A Summary of the New International EAACI/GA2LEN/EDF/WAO Guidelines in Urticaria - Torsten Zuberbier, MD (World Allergy Organization Journal, 2012)
Urticaria is a heterogeneous group of disorders, especially acute urticaria and angiooedema can be a medical emergency. This paper summarizes the EAACI/GA2LEN/EDF/WAO guidelines, the most recent international guidelines from 2009. Patients with urticaria are often not diagnosed and treated appropriately and the guidelines state that clinicians should always aim to provide complete symptom relief. The mainstay of urticaria treatment is the use of modern nonsedating antihistamines, if required up to 4-fold of standard doses. Keywords: urticaria, acute urticaria, guidelines, nonsedating antihistamines